Participation Leadership Style, Workload, and Job Satisfaction for Improving Working Motivation among Nurses in Inpatient Room - Hasyim; Ramadhanil, Ferdy; Indrawati , Ratna (International Journal of Nursing and Health Services (IJNHS), 2022)
Background. Work motivation is essential for employees to contribute to the company positively. The existence of positive work motivation will encourage nurses to give something more, increase productivity, and work effectively and efficiently in hospitals. Objective. The study aimed to analyze the effect of Participation leadership style and workload on the work motivation of inpatient nurses mediated by job satisfaction simultaneously. Method: A explanatory research with a causality approach was applied in this study. Results: The study results showed that the variables of participation leadership style, workload, and job satisfaction positively impacted work motivation with p < .01. Participation leadership style does not positively affect work motivation with a p-value = .138. The workload does not positively impact work motivation, with a p-value = .921. Job satisfaction positively affects work motivation with a p-value < .001. Participation leadership style positively impacts job satisfaction with a p-value <.05. Workload has a positive effect on job satisfaction with a p-value <.05. Conclusion: The variables of participation leadership style and workload have a positive impact on motivation work through job satisfaction